Membangun Dan Mengembangkan Serta Meningkatkan UMKM Di Desa Tenggayun - Irawan Fakhrudin Mahalizikri (LPPM ISNJ Bengkalis, 2019)
Development of the physical sector which continues to advance along with the rapid advancement of science and technology needs to be balanced with the progress of society in nonphysical aspects. So far the progress of science and technology still leaves the community behind on non-physical aspects. Higher Education plays an important role in participating in the success of the National development program. The main objective of national development is the formation of modern Indonesian society but still adhering to the Pancasila and the 1945 Constitution. In Indonesia, the definition of micro small and medium enterprises is regulated in the Republic of Indonesia Law Number 20 of 2008 concerning micro small and medium enterprises. In the formation of this modern society, universities are tasked with creating experts who must have high knowledge and be able to develop their knowledge through technology that can ultimately be utilized by the Indonesian people as a whole. By following the pace of increasingly dynamic development steps to improve human resources both in the utilization and processing of natural resources and human resources. In implementing the knowledge possessed from various disciplines which henceforth can be applied in the midst of the community especially the Tenggayun village in terms of building and developing and enhancing micro, small and medium businesses.